Systematic Representation of Sound Locations in the Primary Auditory Cortex - Razak, Khaleel A. (Society for Neuroscience, 2011)
The primary auditory cortex (A1) is involved in sound localization. A consistent observation in A1 is a clustered representation of binaural properties, but how spatial tuning varies within binaural clusters is unknown. Here, this issue was addressed in A1 of the pallid bat, a species that relies on passive hearing (as opposed to echolocation) to localize prey. Evidence is presented for systematic representations of sound azimuth within two binaural clusters in the pallid bat A1: the binaural inhibition (EI) and peaked (P) binaural interaction clusters. The representation is not a “point-to-point” space map as seen in the superior colliculus, but is in the form of a systematic increase in the area of activated cortex as azimuth changes from ipsilateral to contralateral locations. The underlying substrate in the EI cluster is a systematic representation of the medial boundary of azimuth receptive fields. The P cluster is activated mostly for sounds near the midline, providing a spatial acoustic fovea. Activity in the P cluster falls off systematically as the sound is moved to more lateral locations. Sensitivity to interaural intensity differences predicts azimuth tuning in the vast majority of neurons. Azimuth receptive field properties are relatively stable across intensity over a moderate range (20–40 dB above threshold) of intensities. This suggests that the maps will be similar across the intensities tested. These results challenge the current view that no systematic representation of azimuth is present in A1 and show that such representations are present locally within individual binaural clusters.